Poverty eradication: the need for good citizenship - Naudé, Wim (University of the Free State, 2003)
English: This paper makes use of game theory to argue that poverty and inequality can be understood as the outcome of a repeated game in which the players are caught in a poverty trap, or “prisoners’ dilemma”. They can escape this dilemma by means of cooperation and co-ordination, requiring appropriately designed “institutions” or “game rules”. However, such institutions or game rules may be only a necessary, not a sufficient condition for this. From the perspectives of evolutionary biology and evolutionary psychology a case is made for the indispensability of good citizenship to poverty eradication.

Afrikaans: In hierdie artikel word daar vanuit ’n spelteoretiese perspektief geargumenteer dat armoede en ongelykheid die resultaat is van ’n herhalende spel waarin die spelers in ‘n armoedevalstrik of “prisoniersdilemma” vasgevang is. Hulle kan uit hierdie gevangenskap ontsnap deur koördinering en samewerking waarvoor gepaste “instellings” of “spelreëls” nodig is. Gepaste instellings/spelreëls is egter wel ’n nodige, maar nie ’n voldoende voorwaarde vir koördinering en samewerking nie. Insigte uit die evolusionêre biologie en evolusionêre psigologie word gebruik om te argumenteer dat goeie burgerskap noodsaaklik is vir armoedeverligting.
Keywords: Poverty; Poverty eradication; Citizenship